The impact of melphalan conditioning and CD34+ cell dose and schedule on post-transplant outcomes in AL amyloidosis - Muchtar, Eli; Sanchorawala, Vaishali; Hassan, Hamza; Hegenbart, Ute; Schönland, Stefan; Lee, Hans C.; Qazilbash, Muzaffar; Kin, Andrew; Zonder, Jeffrey; Jacob, Eapen; Buadi, Francis; Dispenzieri, Angela; et al. (American journal of hematology, 2025)
The optimal conditioning schedule and CD34+ cell dose for autologous stem cell transplantation (ASCT) for AL amyloidosis is unknown. Patients (n = 1704) who underwent ASCT for AL amyloidosis between 2003 and 2020 in 9 centers were included. Data on melphalan conditioning dose, number of conditioning days, whether a rest day between conditioning and stem cell infusion was given or not, and infused CD34+ cell dose were collected. Full-dose melphalan (≥ 180 mg/m2) was administered in 63.7% of the patients, and 80.4% had melphalan split into 2-day conditioning. A rest day (day −1) between the conditioning regimen and stem cell infusion was provided in 52.5% of patients. The median infused CD34+ cell count was 4.7 × 106/kg. An infused CD34+ cell count ≥ 4.5 × 106/kg was associated with a shorter time to neutrophil and platelet engraftment. In a nominal regression analysis, full-dose melphalan, 1-day melphalan conditioning, and omitting a rest day between conditioning and stem cell infusion were independent predictors of post-ASCT higher deep hematological response. The median follow-up was 8.6 years, and 38% of patients died. Independent predictors of superior overall survival in multivariate Cox regression analysis included full-dose melphalan, having no rest day, and infused CD34+ cells ≥ 4.5 × 106/kg. Independent predictors of higher day-100 transplant-related mortality (TRM) in nominal logistic regression analysis included poorer performance status, NT-proBNP/BNP ≥ 1800/400 pg/mL, serum albumin < 2.5 g/dL, CD34+ cells < 4.5 × 106/kg, and not having a rest day. In conclusion, 1 day of melphalan conditioning and administration of CD34+ cells ≥ 4.5 × 106/kg are recommended for ASCT in AL amyloidosis.